Commodity Markets Outlook, January 2017 : Investment Weakness in Commodity Exporting Countries - World Bank Group (World Bank, Washington, DC, 2017)
Prices for most industrial commodities continued to rise in the fourth quarter from their lows in early 2016, while most agricultural prices declined. Crude oil prices are forecast to rise to $55 per barrel in 2017 from $43/bbl in 2016 following agreements among some Organization of the Petroleum Exporting Countries (OPEC) producers and non-OPEC producers to limit output in the first half of 2017. Metals prices are projected to rise 11 percent as a result of supply constraints, including large lead and zinc mines closures. Agricultural commodities prices are anticipated to rise slightly in 2017, with increases in oils and meals and raw materials, offset by declines in grains following favorable weather conditions in Europe, North America, and Central Asia. This edition of Commodity Markets Outlook analyzes the recent investment weakness in commodity-exporting emerging market and developing economies (EMDEs) and concludes that the deceleration reflects elevated uncertainty, deteriorated terms of trade, and increased private debt burdens.